Determinants on Share Market Price of Mining Companies (Case Study in Indonesia) - Moh. Taufan Nugroho; Maria; Hakim, Luqman (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The mining industry including coal production has a significant contribution to state income. Therefore, the financial performance must be maintained as well as the market value. The aim of this research is to explore the determinants of share market price of mining sector in Indonesia. Several independent variables are used like corporate social responsibility, good corporate governance, financial performance, and macroeconomic variables. This study uses 22 coal mining companies in 2018 - 2021 by using purposive sampling. The research method used linear multiplier regression by conducting various tests, including descriptive statistics, determination, regression equation, and hypothesis tests. This study finds the Inflation, Exchange Rate, Profitability, and Firm’s Size have a significant effect on Share Market Price. Whereas, Corporate Social Responsibility, Good Corporate Governance, and Liquidity have not an influence on Share Market Price. The research’s usefulness is terribly important for several sides include managers, companies, and policymakers interested in addressing mining companies, improving financial performance and mitigation strategies. The study highlighted that Share Market Price is not only related to internal factors but also external factors, hence it might be obtained of competitive advantage. This study has limitedness, including internal and external factors and research period. It is recommended to enhance it to obtain better results.